Gastrointestinal Bleeding Seminar - Peter Gliatto; Reena Karani (Association of American Medical Colleges, 2010)
Abstract This resource is a third-year seminar on gastrointestinal bleeding. The session is designed to be case-based, so the students should not see the content of the case in advance. Instead, they should be told that the seminar is about gastrointestinal bleeding and should be assigned appropriate background reading ahead of time. They should be instructed to approach this case as though they were involved in an actual clinical encounter. The purpose is to have the students derive the data in the way they would from a real patient, so they can enhance their data-gathering and interpreting skills as they build on their knowledge of gastrointestinal bleeding and its complications. Coming up with a differential diagnosis as they derive the data and then altering the differential based on new data helps them further refine their clinical reasoning skills. A faculty facilitator unfolds the details of the case and, along the way, makes teaching points and explores the students' thought processes. A teaching guide, which only the faculty facilitator receives, contains the case description as well as all of the information needed to answer student questions. This seminar should take 1 hour to conduct. The case is designed to be complex in order to reflect the types of patients that students see on the inpatient setting of academic medical centers. Given the multiple issues involved, students in this exercise are asked to prioritize issues and make decisions in a setting of competing interests. The case also highlights important concepts such as handoffs, sign-out, and communication between care teams. Aside from the general acceptability of this kind of seminar among our students, we have not collected outcomes data.